ECR Enterprise : economic car rental / Muhammad Fakruddin Latif ...[et al.] - Latif, Muhammad Fakruddin; Ahmad Mazuki, Ahmad Afif Irfan; Mohd Yusoff, Muhammad Fazrul Haqqem; Rozlan, Muhammad Aiman Shauki; Abd Razak, Muhammad Amirul Hakim; Zainal Abidin, Ainul Hayat (2014)
Company that rents vehicles to people in need, especially tourists who want to visit tourist places in Malaysia. Our business is located at Pekan Pandak Mayah, Kuah, Langkawi. We would rent a shop there for our office. As there are many companies that provide car rental service, we want to start a company that can attract tourists to rent a car in our company. Moreover, we believe that we can compete with other companies in the past few years. This is because the present-day tourists are always moving from one place to another using public transport. This is because they do not get info about their service or car rental they prefer to use public transport. We will make them so interested in using our services. we also want them to feel comfortable when using our services. Opportunity that this business has the potential of success provide that it is handled efficiently. The people have always needed vehicle to move from one place to another. This is because vehicle is one of the important things in our lives.